A Linguocultural Analysis of Expressive And Stylistic Devices In English And Uzbek Humorous Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article investigates the expressive and stylistic devices used to construct humour in English and Uzbek literature, focusing on K. Jerome’s Three Men in a Boat and Shum bola by Gʻafur Gʻulom. Adopting a linguocultural perspective, the study explores how humour is shaped not only by linguistic form but also by the cultural norms and communicative values embedded within each language. Through qualitative analysis of selected excerpts, the research reveals that while both literatures employ similar stylistic techniques—such as metaphor, irony, euphemism, and exaggeration—their function and usage differ significantly. English humour tends to be self-referential, direct, and psychologically nuanced, while Uzbek humour favours indirectness, cultural symbolism, and social harmony. These differences highlight the essential role of cultural context in humorous expression and suggest that stylistic devices in literature serve both aesthetic and pragmatic purposes. The findings contribute to cross-cultural stylistics and deepen our understanding of humour as a linguistically universal but culturally specific phenomenon.